Immobilized phospholipase A1 carrier material and application thereof in DHA synthesis

By immobilizing phospholipase A1 with the magnetic mesoporous material MnFe2O4-SiO2, the problems of enzyme stability and recycling difficulties in traditional DHA synthesis are solved, and efficient binding of DHA to phospholipids is achieved, with excellent enzyme recovery and reuse performance.

CN119776340APending Publication Date: 2025-04-08SHANDONG UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510037794.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The poor stability and difficulty in recycling of enzymes in traditional DHA synthesis methods limit their application in industrial production, and the enzyme loading and catalytic efficiency of magnetic materials such as MnFe2O4 are low.

Method used

The magnetic mesoporous material MnFe2O4-SiO2 is used as a carrier to immobilize phospholipase A1 (PLA1), and the MnFe2O4-SiO2 composite material is prepared by hydrothermal method and chemical precipitation method, and PLA1 is immobilized on its surface, thereby using an external magnetic field to achieve rapid separation and recovery of enzymes.

Benefits of technology

The catalytic efficiency and recovery performance of the enzyme were significantly improved. The relative enzyme activity of the enzyme remained at 65%~75% after 5 catalytic cycles, and the efficient binding of DHA and phospholipids was achieved, with an incorporation rate of 40%-50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776340A_ABST
    Figure CN119776340A_ABST
Patent Text Reader

Abstract

The invention provides a phospholipid type DHA (Docosahexaenoic Acid) synthesis method based on immobilized phospholipase A1 of a magnetic composite material MnFe2O4-SiO2. The method comprises the following steps: (1) preparing MnFe2O4 magnetic nanoparticles by adopting a hydrothermal method; (2) coating the surface of the MnFe2O4 with SiO2 through a chemical precipitation method, so as to prepare a MnFe2O4-SiO2 composite material; (3) by using phospholipase A1 (PLA1) as a catalytic enzyme, immobilizing PLA1 on the surface of the MnFe2O4-SiO2 composite material through a chemical crosslinking or physical adsorption method; (4) under optimized reaction conditions, catalyzing free fatty acid to react with phospholipid by the immobilized enzyme to synthesize phospholipid type DHA; and (5) separating and recovering the immobilized enzyme through an external magnetic field, and after the immobilized enzyme is repeatedly used for 5-10 times, keeping the catalytic activity of 65-75%. According to the method, the stability and reusability of the enzyme can be remarkably improved, the production cost is reduced, and meanwhile, the method is applied to catalytic synthesis of the phospholipid DHA and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of magnetic nano-functional materials, and in particular to a method for catalyzing the synthesis of phospholipid-type DHA by immobilizing phospholipase A1 based on the magnetic material MnFe2O4-SiO2. Background Art

[0002] DHA is an omega-3 polyunsaturated fatty acid with important biological activity, which is widely used in food, health products and medicine. The traditional DHA synthesis method has problems such as poor enzyme stability and difficulty in recycling, which limits its application in industrial production. Immobilized enzyme technology can significantly improve the stability of the enzyme and facilitate multiple recycling, thereby reducing production costs and improving economic benefits.

[0003] Magnetic materials, as immobilized enzyme carriers, have the advantage of being able to achieve rapid separation and recovery under the action of an external magnetic field, and are therefore widely used in the study of immobilized enzymes. However, magnetic materials such as MnFe2O4 usually have low enzyme loading and poor catalytic efficiency. Therefore, how to improve the immobilization efficiency of magnetic materials for phospholipase A1 (PLA1) and enhance its catalytic performance has become a research difficulty in this field.

[0004] Mesoporous materials (such as SiO2) have large specific surface area and good surface functionalization properties, which can provide a better fixation environment for enzymes. Combining magnetic materials with SiO2 to form a MnFe2O4-SiO2 composite material and fixing phospholipase A1 on its surface is expected to significantly improve the catalytic efficiency and recovery performance of the enzyme.

[0005] Advantages of the invention

[0006] 1. Highly efficient enzyme immobilization and recovery performance. The present invention uses the magnetic nanocomposite material MnFe2O4-SiO2 as a carrier to immobilize phospholipase A1 (PLA1). The magnetic composite material has excellent magnetic response performance, and can achieve rapid separation and recovery of immobilized enzymes under the action of an external magnetic field, thereby simplifying the enzyme recovery process. Through the external magnetic field, the immobilized enzyme can be efficiently and conveniently enriched and separated from the reaction system, significantly improving the recovery rate and reuse efficiency of the enzyme and reducing production costs.

[0007] 2. Improve the stability and reusability of the enzyme. After 5 catalytic cycles, the relative enzyme activity of the immobilized enzyme (compared with the free enzyme) remained at 65%~75% of the initial value. This result shows that the magnetic composite material MnFe2O4-SiO2 greatly improves the reusability of the enzyme and prolongs the service life of the enzyme.

[0008] 3. Suitable for efficient synthesis of phospholipid-type DHA. The method of the present invention successfully applies magnetic immobilized phospholipase A1 to the synthesis of phospholipid-type DHA. Under optimized reaction conditions, DHA can be efficiently combined with phospholipids, and the incorporation rate reaches 40%-50%, ensuring the high efficiency of the reaction and the high purity of the product. The method can complete the transesterification reaction of DHA under mild conditions, avoiding the byproducts and environmental pollution that may be caused by traditional chemical methods.

[0009] 4. Suitable for large-scale industrial applications. The immobilized enzyme system provided by the present invention can use an external magnetic field to control the distribution and recovery of the enzyme, replacing the traditional mechanical stirring and separation methods, greatly improving the reaction efficiency. This makes the method have a wide range of application prospects in large-scale industrial production, especially suitable for continuous operation, and can meet the needs of modern production. Summary of the invention

[0010] The present application provides a method for catalyzing the synthesis of phospholipid-type DHA by immobilizing phospholipase A1 on magnetic mesoporous material MnFe2O4-SiO2. The method significantly improves the stability and catalytic efficiency of the enzyme by optimizing the enzyme immobilization conditions and catalytic conditions, and solves the problems of difficulty in enzyme recovery and reduced activity in enzyme-catalyzed reactions.

[0011] A method for synthesizing phospholipid-type DHA based on immobilized phospholipase A1 on a magnetic composite material MnFe2O4-SiO2, characterized by comprising the following steps: 1) MnFe2O4 magnetic nanoparticles were prepared by hydrothermal method; (2) SiO2 was coated on the surface of MnFe2O4 by chemical precipitation method to obtain MnFe2O4-SiO2 composite material; (3) Phospholipase A1 (PLA1) was used as catalytic enzyme, and PLA1 was immobilized on the surface of the MnFe2O4-SiO2 composite material by fixing for 2-20 h and adding 2-10 mL of enzyme; (4) Under appropriate reaction conditions, the immobilized enzyme was used to catalyze the synthesis of phospholipid-type DHA, with a reaction substrate ratio (free fatty acid: soybean lecithin) of 2:1-18:1 and a water addition amount of 0-8%; (5) After the reaction was completed, the MnFe2O4-SiO2@PLA1 immobilized enzyme was separated and recovered by applying an external magnetic field. (6) After 5 cycles of use, the relative enzyme activity (compared with the free enzyme) of the immobilized enzyme in the magnetic nanocomposite material remained at 65%~75% of the initial value. The above method can achieve a DHA incorporation rate of 40%-50%.

[0012] Specific implementation method.

[0013] Preparation of magnetic nanomaterial MnFe2O4, MnFe2O4 magnetic nanoparticles were synthesized by hydrothermal method. First, MnCl2·4H2O and FeCl3·6H2O were dissolved in deionized water at a molar ratio of 1:2 to prepare a 0.3 mol / L metal salt solution. Then, 4.5-5 g of anhydrous sodium acetate was added to the solution and dissolved. Next, 1.2-2.0 mol / LNaOH solution was added dropwise to adjust the pH value to about 13. The resulting precursor solution was transferred to a 100 mL polytetrafluoroethylene liner. The liner was sealed and placed in a reactor and reacted at 180-200°C for 10-12 h. After cooling to room temperature, the black precipitate produced was separated using a neodymium iron boron (NdFeB) magnet. Finally, the precipitate was washed with ethanol and deionized water several times to remove any impurities and then dried under vacuum at 80 °C for 6–10 h to obtain the final MnFe2O4 nanoparticles.

[0014] The MnFe2O4-SiO2 core-shell material was prepared by chemical precipitation. First, 0.1 g of MnFe2O4 was dispersed in 100 mL of anhydrous ethanol and subjected to ultrasonic treatment. After ensuring complete dispersion, 1.5 mL of ammonia water and 25 mL of deionized water were added to the solution and then stirred evenly. Then, 0.5 mL of tetraethyl orthosilicate (TEOS) was added dropwise to the mixture and reacted with magnetic stirring at room temperature for 8-14 hours. Afterwards, the product was separated using a NdFeB magnet and washed 3-5 times with anhydrous ethanol and deionized water to remove any residual reagents. Subsequently, the composite material was vacuum dried at 60-80°C for 6-10 h and finally ground to obtain a core-shell structured MnFe2O4-SiO2 (MnFe2O4:SiO2=1:5).

[0015] To prepare the immobilized PLA1, 200.0 mg of the MnFe2O4-SiO2 composite support was placed in a 50 mL centrifuge tube. Then, different volumes of 29.5 mg / mL PLA1 solution were added to the test tube, prepared by diluting with phosphate buffer at pH 2-10. The mixture was incubated in a shaker at 180 rpm at a set temperature of 10-50°C for the specified duration. After immobilization, the immobilized enzyme was separated by a permanent magnet and washed to remove the unimmobilized enzyme, finally obtaining the MnFe2O4-SiO2@PLA1 immobilized enzyme.

[0016] Catalytic synthesis reaction: In the reaction system, add phospholipid substrate (such as lecithin) and free fatty acids, then add 100 mg of immobilized enzyme MnFe2O4-SiO2@PLA1, set the reaction temperature to 30-50°C, and the reaction time to 12-36 hours. During the reaction, adjust the solvent system to improve the reaction efficiency.

[0017] For the recovery and reuse of immobilized enzymes, a magnet is placed outside the container to allow the immobilized enzyme particles to adsorb to the container wall. After pouring out the supernatant, the particles are washed 2-3 times with phosphate buffer (pH=7.0), and the magnetic field separation operation is repeated until there is no residue in the supernatant. The immobilized enzyme is separated from the reaction system. The enzyme is then cleaned and reused. After 5-10 cycles, the relative enzyme activity of the immobilized enzyme (compared with the free enzyme) remains at 65%-75% of the initial value. This proves that this method has good enzyme recovery and reuse performance.

[0018] Technical Effects The present invention improves the immobilization efficiency and catalytic performance of phospholipase A1 by using the magnetic mesoporous material MnFe2O4-SiO2. Compared with the traditional immobilized enzyme method, the immobilized enzyme of the present invention has the following advantages: The activity retention rate of the immobilized enzyme is high, which can effectively improve the synthesis efficiency of phospholipid DHA / DPA; The immobilized enzyme can be quickly recovered under the action of an external magnetic field, which greatly reduces the loss of enzyme during the catalytic process; The stability of the immobilized enzyme is improved, and it can maintain a high catalytic activity in multiple cycles, thus reducing production costs.

[0019] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.

[0020] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each embodiment, enumeration is only used as a representative group and should not be interpreted as exhaustive. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Attached Figure 1 It is the XRD spectrum of MnFe2O4, MnFe2O4-SiO2 and MnFe2O4-SiO2@PLA1 materials prepared in Examples 1, 2 and 3; Attached Figure 2This is a flow chart of the synthesis of phospholipid-type DHA catalyzed by the MnFe2O4-SiO2@PLA1 immobilized enzyme prepared in Examples 1, 2, and 3; Figure 3 is a SEM image of the MnFe2O4-SiO2@PLA1 immobilized enzyme prepared in Example 1; FIG4 is a SEM image of the MnFe2O4-SiO2@PLA1 immobilized enzyme prepared in Example 2; FIG5 is a SEM image of the MnFe2O4-SiO2@PLA1 immobilized enzyme prepared in Example 3.

[0022] Example

[0023] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application will be apparent to those skilled in the art. All reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0024] Example 1

[0025] The method for synthesizing phospholipid-type DHA based on immobilized phospholipase A1 on the magnetic composite material MnFe2O4-SiO2 prepared in this embodiment is as follows:

[0026] Preparation of magnetic nanomaterials MnFe2O4, MnFe2O4 magnetic nanoparticles were synthesized by hydrothermal method. First, MnCl2·4H2O and FeCl3·6H2O were dissolved in deionized water at a molar ratio of 1:2 to prepare a 0.3 mol / L metal salt solution. Then, 4.5 g of anhydrous sodium acetate was added to the solution and dissolved. Next, 1.2 mol / L NaOH solution was added dropwise to adjust the pH to about 13. The resulting precursor solution was transferred to a 100 mL polytetrafluoroethylene liner. The liner was sealed and placed in a reactor and reacted at 180 °C for 10 h. After cooling to room temperature, the resulting black precipitate was separated using a neodymium iron boron (NdFeB) magnet. Finally, the precipitate was washed several times with ethanol and deionized water to remove any impurities, and then vacuum dried at 80 °C for 6 h to obtain the final MnFe2O4 nanoparticles.

[0027] The MnFe2O4-SiO2 core-shell material was prepared by chemical precipitation. First, 0.1 g of MnFe2O4 was dispersed in 100 mL of anhydrous ethanol and subjected to ultrasonic treatment. After ensuring complete dispersion, 1.5 mL of ammonia water and 25 mL of deionized water were added to the solution and then stirred evenly. Then, 0.5 mL of tetraethyl orthosilicate (TEOS) was added dropwise to the mixture and reacted with magnetic stirring at room temperature for 8 h. Afterwards, the product was separated using a NdFeB magnet and washed three times with anhydrous ethanol and deionized water to remove any residual reagents. Subsequently, the composite material was vacuum dried at 60°C for 6 h and finally ground to obtain a core-shell structured MnFe2O4-SiO2 (MnFe2O4:SiO2=1:5).

[0028] To prepare the immobilized PLA1, 200.0 mg of the MnFe2O4-SiO2 composite support was placed in a 50 mL centrifuge tube. Then, 6 mL of a 29.5 mg / mL PLA1 solution prepared by diluting with a phosphate buffer with a pH of 6 was added to the test tube. The mixture was immobilized at 30 °C for 4 h at a speed of 180 rpm in a shaker. After immobilization, the immobilized enzyme was separated by a permanent magnet and washed to remove the unimmobilized enzyme, finally obtaining the MnFe2O4-SiO2@PLA1 immobilized enzyme.

[0029] The XRD spectra of MnFe2O4, MnFe2O4-SiO2 and MnFe2O4-SiO2@PLA1 prepared in this example are shown in the attached Figure 1 As shown, it shows that the composite material was successfully prepared.

[0030] Catalytic synthesis reaction: In the reaction system, phospholipid substrate (such as lecithin) and free fatty acids were added, with the ratio of free fatty acids to lecithin being 10:1, and the amount of water added being 4%. Then, 100 mg of immobilized enzyme MnFe2O4-SiO2@PLA1 was added, and the reaction temperature was set to 40°C, and the reaction time was 24 hours. During the reaction, the solvent system was adjusted to improve the reaction efficiency.

[0031] The main flow chart of this embodiment is shown in the attached Figure 2 shown.

[0032] For the recovery and reuse of immobilized enzymes, a magnet was placed outside the container to allow the immobilized enzyme particles to adsorb to the container wall. After pouring out the supernatant, the particles were washed three times with phosphate buffer (pH=7.0), and the magnetic field separation operation was repeated until there was no residue in the supernatant. The immobilized enzyme was separated from the reaction system. The enzyme was then cleaned and reused. After five cycles of use, the catalytic activity of the immobilized enzyme could still be maintained at more than 60%, proving that this method has good enzyme recovery and reuse performance.

[0033] The DHA incorporation rate was 36.76% using a phospholipid DHA synthesis method based on the magnetic composite material MnFe2O4-SiO2 immobilized phospholipase A1. Figure 3 The SEM images shown show that the surface of the immobilized enzyme is uniform and smooth, and has good dispersibility. The phospholipid-type DHA synthesized by this method has high purity and good synthesis efficiency, which verifies the application potential of the method of the present invention in DHA synthesis.

[0034] Example 2

[0035] The method for synthesizing phospholipid-type DHA based on the magnetic composite material MnFe2O4-SiO2 immobilized phospholipase A1 prepared in this embodiment is as follows:

[0036] Preparation of magnetic nanomaterials MnFe2O4, MnFe2O4 magnetic nanoparticles were synthesized by hydrothermal method. First, MnCl2·4H2O and FeCl3·6H2O were dissolved in deionized water at a molar ratio of 1:2 to prepare a 0.3 mol / L metal salt solution. Then, 5 g of anhydrous sodium acetate was added to the solution and dissolved. Next, 1.2 mol / L NaOH solution was added dropwise to adjust the pH value to about 13. The resulting precursor solution was transferred to a 100 mL polytetrafluoroethylene liner. The liner was sealed and placed in a reactor and reacted at 180°C for 12 h. After cooling to room temperature, the resulting black precipitate was separated using a neodymium iron boron (NdFeB) magnet. Finally, the precipitate was washed several times with ethanol and deionized water to remove any impurities, and then vacuum dried at 80 °C for 8 h to obtain the final MnFe2O4 nanoparticles.

[0037] The MnFe2O4-SiO2 core-shell material was prepared by chemical precipitation. First, 0.1 g of MnFe2O4 was dispersed in 100 mL of anhydrous ethanol and subjected to ultrasonic treatment. After ensuring complete dispersion, 1.5 mL of ammonia water and 25 mL of deionized water were added to the solution and then stirred evenly. Then, 0.5 mL of tetraethyl orthosilicate (TEOS) was added dropwise to the mixture and reacted with magnetic stirring at room temperature for 10 h. Afterwards, the product was separated using a NdFeB magnet and washed 3 times with anhydrous ethanol and deionized water to remove any residual reagents. Subsequently, the composite material was vacuum dried at 60°C for 6 h and finally ground to obtain a core-shell structured MnFe2O4-SiO2 (MnFe2O4:SiO2=1:5).

[0038] To prepare the immobilized PLA1, 200.0 mg of the MnFe2O4-SiO2 composite support was placed in a 50 mL centrifuge tube. Then, 6 mL of a 29.5 mg / mL PLA1 solution prepared by diluting with a phosphate buffer with a pH of 6 was added to the test tube. The mixture was immobilized at 10 °C for 4 h at 180 rpm in a shaker. After immobilization, the immobilized enzyme was separated by a permanent magnet and washed to remove the unimmobilized enzyme, finally obtaining the MnFe2O4-SiO2@PLA1 immobilized enzyme.

[0039] The XRD spectra of MnFe2O4, MnFe2O4-SiO2 and MnFe2O4-SiO2@PLA1 prepared in this example are shown in the attached Figure 1 As shown, it shows that the composite material was successfully prepared.

[0040] In the reaction system, phospholipid substrate (such as lecithin) and free fatty acids were added, with a free fatty acid: lecithin ratio of 10:1, 4% water, and then 100 mg of immobilized enzyme MnFe2O4-SiO2@PLA1 was added. The reaction temperature was set to 40°C and the reaction time was 24 hours. During the reaction, the solvent system was adjusted to improve the reaction efficiency.

[0041] The main flow chart of this embodiment is shown in the attached Figure 2 shown.

[0042] For the recovery and reuse of immobilized enzymes, a magnet was placed outside the container to allow the immobilized enzyme particles to adsorb to the container wall. After pouring out the supernatant, the particles were washed three times with phosphate buffer (pH=7.0), and the magnetic field separation operation was repeated until there was no residue in the supernatant. The immobilized enzyme was separated from the reaction system. The enzyme was then cleaned and reused. After five cycles of use, the catalytic activity of the immobilized enzyme could still be maintained at more than 60%, proving that this method has good enzyme recovery and reuse performance.

[0043] Attached Figure 4 The SEM image shows that the immobilized enzyme particles have a uniform structure and a rounded shape. By using the MnFe2O4-SiO2 composite material to immobilize phospholipase A1, the DHA incorporation rate is 22.46%. This result shows that the method of the present invention can effectively catalyze the synthesis of phospholipid-type DHA and has good reusability.

[0044] Example 3

[0045] The method for synthesizing phospholipid-type DHA based on immobilized phospholipase A1 on the magnetic composite material MnFe2O4-SiO2 prepared in this embodiment is as follows:

[0046] Preparation of magnetic nanomaterials MnFe2O4, MnFe2O4 magnetic nanoparticles were synthesized by hydrothermal method. First, MnCl2·4H2O and FeCl3·6H2O were dissolved in deionized water at a molar ratio of 1:2 to prepare a 0.3 mol / L metal salt solution. Then, 4.5 g of anhydrous sodium acetate was added to the solution and dissolved. Next, 2.0 mol / L NaOH solution was added dropwise to adjust the pH value to about 13. The resulting precursor solution was transferred to a 100 mL polytetrafluoroethylene liner. The liner was sealed and placed in a reactor and reacted at 180°C for 10 h. After cooling to room temperature, the resulting black precipitate was separated using a neodymium iron boron (NdFeB) magnet. Finally, the precipitate was washed several times with ethanol and deionized water to remove any impurities, and then vacuum dried at 80 °C for 10 h to obtain the final MnFe2O4 nanoparticles.

[0047] The MnFe2O4-SiO2 core-shell material was prepared by chemical precipitation. First, 0.1 g of MnFe2O4 was dispersed in 100 mL of anhydrous ethanol and subjected to ultrasonic treatment. After ensuring complete dispersion, 1.5 mL of ammonia water and 25 mL of deionized water were added to the solution and then stirred evenly. Then, 0.5 mL of tetraethyl orthosilicate (TEOS) was added dropwise to the mixture and reacted with magnetic stirring at room temperature for 12 h. Afterwards, the product was separated using a NdFeB magnet and washed 3 times with anhydrous ethanol and deionized water to remove any residual reagents. Subsequently, the composite material was vacuum dried at 60°C for 10 h and finally ground to obtain a core-shell structured MnFe2O4-SiO2 (MnFe2O4:SiO2=1:5).

[0048] To prepare the immobilized PLA1, 200.0 mg of the MnFe2O4-SiO2 composite support was placed in a 50 mL centrifuge tube. Then, 6 mL of a 29.5 mg / mL PLA1 solution prepared by diluting with a phosphate buffer with a pH of 6 was added to the test tube. The mixture was immobilized at 30 °C for 4 h at a speed of 180 rpm in a shaker. After immobilization, the immobilized enzyme was separated by a permanent magnet and washed to remove the unimmobilized enzyme, finally obtaining the MnFe2O4-SiO2@PLA1 immobilized enzyme.

[0049] The XRD spectra of MnFe2O4, MnFe2O4-SiO2 and MnFe2O4-SiO2@PLA1 prepared in this example are shown in the attached Figure 1 As shown, it shows that the composite material was successfully prepared.

[0050] In the reaction system, phospholipid substrate (such as lecithin) and free fatty acids were added, with a free fatty acid: lecithin ratio of 10:1, 4% water, and then 100 mg of immobilized enzyme MnFe2O4-SiO2@PLA1 was added. The reaction temperature was set to 35°C and the reaction time was 24 hours. During the reaction, the solvent system was adjusted to improve the reaction efficiency.

[0051] The main flow chart of this embodiment is shown in the attached Figure 2 shown.

[0052] For the recovery and reuse of immobilized enzymes, a magnet was placed outside the container to allow the immobilized enzyme particles to adsorb to the container wall. After pouring out the supernatant, the particles were washed three times with phosphate buffer (pH=7.0), and the magnetic field separation operation was repeated until there was no residue in the supernatant. The immobilized enzyme was separated from the reaction system. The enzyme was then cleaned and reused. After five cycles of use, the catalytic activity of the immobilized enzyme could still be maintained at more than 60%, proving that this method has good enzyme recovery and reuse performance.

[0053] Phospholipid DHA was synthesized by immobilizing phospholipase A1 on the magnetic composite material MnFe2O4-SiO2, and a DHA incorporation rate of 24.62% was obtained. Figure 5 The SEM images in further verify the spherical surface morphology of the immobilized enzyme. The results of this embodiment show that the method of the present invention maintains good catalytic efficiency in multiple reaction cycles and has significant economic benefits.

[0054] Summarize The present invention provides a method for immobilizing phospholipase A1 based on MnFe2O4-SiO2, which can efficiently synthesize phospholipid-type DHA / DPA and has excellent enzyme stability and recovery performance. The technology can be applied to the fields of food, medicine and cosmetics, and has broad industrial prospects.

[0055] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. An immobilized enzyme carrier for the synthesis of phospholipid-type DHA, characterized in that: The carrier is a MnFe2O4-SiO2 composite material, and the molar ratio of MnFe2O4 to SiO2 is 1:(0.5-2); phospholipase A1 (PLA1) is fixed on the surface of the carrier, and the fixation rate of PLA1 is 60%-80%; the carrier is magnetic and can be separated and recovered under an external magnetic field of 100-500 Oe; the surface of the carrier is hydrophilic.

2. The immobilized enzyme carrier according to claim 1, characterized in that The incorporation rate of the immobilized enzyme-catalyzed synthesis of phospholipid-type DHA is 40%-50%.

3. A method for preparing the immobilized enzyme carrier according to claim 1 or 2, characterized in that: The following steps are involved: (1) MnFe2O4 magnetic nanoparticles were prepared by a hydrothermal method. MnCl2·4H2O and FeCl3·6H2O were dissolved in deionized water in a molar ratio of 1:2 to prepare a metal salt solution. Subsequently, anhydrous sodium acetate was added and fully dissolved. NaOH solution was slowly added dropwise to adjust the pH of the solution to alkaline. The mixed solution was transferred to a polytetrafluoroethylene liner. The liner was sealed and placed in a reactor and placed in an oven at a certain temperature for a certain period of time for hydrothermal reaction. After the reaction was completed, it was cooled to room temperature and separated by a magnet to obtain a black precipitate. Finally, the precipitate was repeatedly washed with ethanol and deionized water to remove impurities, and then dried to obtain MnFe2O4 nanoparticles. (2) SiO2 was coated on the surface of MnFe2O4 by chemical precipitation method. MnFe2O4 was dispersed in anhydrous ethanol, and ammonia and deionized water were added and stirred evenly. Then TEOS was added dropwise and stirred at room temperature to form a SiO2 shell. After the reaction, the product was separated by magnet and washed to remove impurities. Finally, it was dried and ground to obtain a MnFe2O4-SiO2 composite material. (3) Immobilizing PLA1 on the surface of the MnFe2O4-SiO2 composite material under specific conditions: mixing 200 mg of the MnFe2O4-SiO2 composite carrier with an appropriate amount of PLA1 solution, adjusting the appropriate pH value, and immobilizing it in an air bath shaker at a speed of 120-180 rpm and a set temperature for a period of time; after immobilization, separating the immobilized enzyme using a magnet, and washing with a buffer solution until no free enzyme remains, and finally storing the immobilized enzyme at 4°C for future use.

4. The method according to claim 3, characterized in that: In step (1), the conditions for the hydrothermal reaction are: oven temperature 180-200°C, reaction time 10-12 h; In step (3), the fixing conditions are: PLA1 amount is 2-10 mL, pH value is 2-10, fixing temperature is 10-50°C, and fixing time is 2-20 h.

5. A method for synthesizing phospholipid-type DHA using the immobilized enzyme carrier according to claim 1 or 2, characterized in that: The following steps are involved: (1) Under specific reaction conditions, the immobilized enzyme is used to catalyze the synthesis of phospholipid-type DHA, the surfactant sodium dodecyl sulfate (AOT) is dissolved in n-hexane, a phosphate buffer is added to form a microemulsion system, and then free fatty acids and soybean lecithin at a certain substrate ratio are added, and a certain amount of water is added, and stirred until completely dissolved; 100 mg of MnFe2O4-SiO2@PLA1 is added, and the reaction is carried out for a certain time at a set temperature and 150-200 rpm in an air bath shaker; the enzyme is separated by magnetic force, the product is purified by rotary evaporation, and the product is washed with acetone and then evaporated to synthesize phospholipid-type DHA; (2) After the reaction is completed, place a magnet outside the container to allow the immobilized enzyme particles to adsorb to the container wall. After pouring out the supernatant, wash the particles 2 to 3 times with phosphate buffer (pH = 7.0). Repeat the magnetic field separation operation until there is no residue in the supernatant. The recovered immobilized enzyme is then subjected to the operation in (1) to verify the relative enzyme activity of the immobilized enzyme after the cycle.

6. The method according to claim 5, characterized in that: In step (1), the reaction conditions are: reaction substrate ratio (free fatty acid: soybean lecithin) is 2:1-18:1, water addition amount is 0-8%, reaction temperature is 30-50°C, and reaction time is 12-36 h; In step (2), the strength of the applied magnetic field is 100-500 Oe.

7. The method according to claim 5 or 6, characterized in that: After the immobilized enzyme is used for 5-10 cycles, its relative enzyme activity (compared with the free enzyme) is maintained at 65%-75% of the initial value.

Citation Information

Cited By

  • Application of immobilized phospholipase A1 in preparation of phospholipid DHA

    CN120041517A